Structural, physicochemical and functional properties of dietary fibers from tea residue modified by steam explosion - Xing, Yunhao; Zhou, Yunmeng; Kuang, Chuyu; Luo, Kaiyun; Cheng, Yunhui; Wang, Xufeng; Wang, Shaoyun (Frontiers in Sustainable Food Systems, 2024)
Effects of steam explosion (SE) treatment (0.3-1.0 MPa, 30-90s) on the physicochemical and functional properties of dietary fiber (DF) extracted from tea residue were investigated. Results showed that SE led to the formation of porous and less compact microstructures of tea residues.Compared with the control sample (12.41 g/100 g), the content of soluble dietary fibre (SDF) was markedly increased by SE, reaching the maximum of 23.03 g/100 g when steam explored at 0.5 MPa for 90 s, due to the degradation of insoluble dietary fibre (IDF). The physicochemical and functional properties were significantly influenced by SE treatments. IDF exhibited decreased water holding capacity (WHC), swelling capacity (SC), oil holding capacity (OHC) after SE, whereas the physicochemical properties of SDF from SE-treated tea residues (0.3 MPa, 90s) were greatly improved. The glucose absorption capacity (GAC), cholesterol adsorption capacity (CAC), and nitrite ion adsorption capacity (NIAC) of both IDF and SDF showed trends of first increasing and then decreasing, indicating that excessive SE treatment resulted in poor properties of DF. These findings are of great value for the high-value utilization of agricultural by-product and development of functional foods.